Ring Keratitis From Topical Anesthetic Abuse After Laser Epithelial Keratomileusis. (September 2018) - Mergen, Burak; Ozdamar, Akif; Sarici, Ahmet Murat
Abstract : Abstract: A 28-year-old man underwent laser epithelial keratomileusis for the correction of myopia in both eyes. The patient subsequently had delayed corneal epithelial healing in both eyes and ring infiltrate in the left eye (LE). Corneal scrapings were obtained from the ocular surface and subjected to microscopic examination and culture. On identifying and preventing the use of topical proparacaine, the corneal epithelium healed in both eyes after the use of eye pressure patches. The ring infiltrate resolved in the patient's LE, leaving minor opacity at the inferior cornea. Refractive surgeons should consider the possibility of topical anesthetic abuse in cases of corneal ring infiltrates. The resulting prognosis can be excellent after the rapid removal of inciting agents and the application of appropriate treatments.